Application of Progressive Muscle Relaxation Technique to Reduce Blood Glucose Levels in Elderly with Diabetes Mellitus - Putra, Ricky Aprileo Pratama; Susumaningrum, Latifa Aini; Rasni, Hanny; Ardani, Ni Ketut (Jurnal Kesehatan Komunitas Indonesia, 2024)
Diabetes mellitus is a metabolic disease which is often found in the elderly caused by a degenerative process. Progressive muscle relaxation technique is one of the non-pharmacological therapy to decrease blood glucose levels in diabetes mellitus. This case study aimed to analyzed the effect of progressive muscle relaxation technique on problem of instability of blood glucose levels in elderly. This research design is case study. The sample of this research is one elderly who had diabetes mellitus type 2. The data collection by measuring blood glucose levels during pre-intervention in the morning and post-intervention in the afternoon. The elderly had intervention twice a day for 20 minutes and forward until 5 days. Data collected and processed by using statistical T-test dependent. The elderly with diabetes mellitus type 2 given progressive muscle relaxation technique experienced a decrease in blood glucose levels from pre to post intervention with p-value 0.005 which means it is significant. The application of progressive muscle relaxation technique given to the elderly affect to decrease blood glucose levels in the outcome of pre and post intervention.